Advances in Genetic Research in Systemic Lupus Erythematosus: Trend Analysis, Global Collaboration, and Bibliometric Perspectives - Rahmawati, Desti; Isrovanigoro, Isrovanigoro; Kurniawan, Alvin; Prasetyaning Amukti , Danang; Salamah , Nina; Adikusuma, Wirawan; Chong, Rockie; Muhammad Irham , Lalu (Scripta Medica, 2025)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease affecting multiple organs and systems in the body. SLE manifestations result from lymphopenia, thrombotic thrombocytopenic purpura, thrombocytopaenia, autoimmune haemolytic anaemia, myelofibrosis and leucopoenia. SLE triggers the activation of both innate and adaptive immune responses. This process is initiated by T cells activating autoreactive B cells, leading to the accumulation of immune complexes in tissues. Consequently, an autoimmune cascade occurs, which can either affect a single organ or cause widespread systemic complications. Bibliometric analysis used Vosviewer 1.6.16 and the Biblioshiny R tool to create and display bibliometric maps by obtaining relevant journals related to SLE through the SciVerse Scopus database from 1981 to 2025. The results obtained in the form of journal document types using English with keywords in the form of SLE which shows globally. The United States is the country that produces the most research related to SLE genomics and the highest publication collaboration along with contributing citations at the global first level. Lupus was the journal source that discusses the most genomic studies in SLE disease and Anhui Medical University was the most data affiliation of 131 documents. The increasing number of publications on genomics in SLE from 1981 to 2025 indicates a growing interest in researching and writing about this topic. This trend reflects the evolving understanding of SLE's genetic underpinnings and the potential for advancements in diagnosis, treatment and precision medicine.